The requirement of grouping technique in English lesson in meeting the demand of philosophy of education in Malaysia - Hassan, Aminuddin; Sulaiman, Tajularipin; Zainal Abiddin, Norhasni (The Journal of International Social Research, 2009)
The purpose of this paper is to discuss the need of grouping techniques in English language lesson in order for the school students to use the language efficiently and confidently. This is one of the available approaches used in meeting the demand of philosophy of education in Malaysia. The application of the techniques is through grouping activities which will be able to stimulate and persuade the interest of study among students. Through these activities, the involvement of student in class is increased. By comparing the individuals learning, student is more active and energetic during studies in group. In addition, learning in grouping is more affective to stimulate and strike the values such as motivation, confidence and diligent.